Tracer Study of Master of Management at Private University in Jakarta - Indonesia - Risqiani, Renny; Margaretha, Farah; Kurniawati; Nilasari, B. Medina; Walidaeni, Ihsanul (Archives of Business Research, 2024)
This study aims to determine the profile of alumni of the Master of Management Study Program at a private university in West Jakarta. The respondents of this study were alumni of the study program who graduated in 2021-2022. The type of research used is descriptive research with a quantitative approach. The data used is primary data collected through surveys by distributing questionnaires to respondents. The data is processed using SPSS software. This tracer study is used to determine the position of graduates who have been absorbed in the world of work obtained from the latest conditions related to the position of the work field, the length of time waiting for alumni since graduation, and the suitability between the field of knowledge obtained and the profession at the last time. The results of the tracer study can be used to prepare graduates according to the competencies needed in the world of work.